Heritage tourism landscape: revitalizing the genus loci of 'Batu Arang Heritage Town', Selangor by promoting the heritage value through heritage trail environment/ Ezazul Firdaus Ahmad Jamal - Ahmad Jamal, Ezazul Firdaus (2017)
Batu Arang is a second largest city in Malaya before WWII era and it is a largest coal mining production for commercializing. Batu Arang are located a line between Kuala Selangor and Rawang, Selangor. This paper reveals the potential of heritage tourism landscape in Batu Arang and shows the role of tourism in heritage preservation and conservation. This study also shows that Batu Arang highlights the strength of the uniqueness of the town through their genus loci of abandoned mining collieries especially for the purpose of 'heritage trail'. This research is an ethnographic research, using qualitative methods. The mining collieries have become a product of heritage trial environment. Linking tourism with this heritage trail environment will benefit the local economy. The main idea in heritage tourism landscape is to revitalize the genus loci of Batu Arang heritage town, to promote the heritage value and to reach economic benefits.